The Study of Removal of Polyvinyl Chloride (PVC) Particles from Wastewater through Electrocoagulation - Ramadani, Azaria Ivana; Fardiyah, Qonitah; Rumhayati, Barlah (Indonesian Journal of Chemistry, 2024)
Plastic was produced massively, especially using polyvinyl chloride (PVC) as a raw material. Unfortunately, this condition cause affects the environment, which creates a new pollutant issue. It is essential to study the removal of PVC microplastics in current water treatment processes. The study of wastewater treatment can be achieved using electrocoagulation, which has several benefits, including low-cost, simple chemicals, and accessible equipment operation. This research investigated the study of the removal of PVC microplastics from wastewater by electrocoagulation. The new potential of the electrocoagulation technique using Al-Al electrodes was studied systematically at various variations, i.e., electrolysis time, electrolyte concentration, initial pH, coagulation speed, and electrolyte type. The results showed that the PVC microplastics removal efficiency reached 100% after electrolysis for 60 min, electrolyte concentration of 0.01 mol/L, initial pH of 7, coagulation speed of 500 rpm, the type of electrolyte used was NaCl at a flocculation speed. These optimum conditions also reduced the value of turbidity of wastewater samples from 1.39 ± 0.02 to 1.10 ± 0.05 NTU. The results of this study provide an engineering perspective in optimizing operational parameters for removing PVC microplastics in aquatic environments.